A self-powered porous ZnS/PVDF-HFP mechanoluminescent composite film that converts human movement into eye-readable light. Issue 12 (7th March 2018) - Li, Haitao; Zhang, Yihe; Dai, Han; Tong, Wangshu; Zhou, Yan; Zhao, Junfeng; An, Qi
Abstract : A facile self-powered electroluminescent material effectively converts mechanical vibration into light visible to the naked eye. Abstract : This study reports on a self-powered mechanoluminescent flexible film that converts human movement into green, yellow, and white light that are visible to the naked eye. The film is simply a highly porous composite material that was prepared using a piezoelectric polymer and ZnS luminescent powders. The highly effective mechanoluminescence capabilities stem from both the film's porous structure and the strong interactions between poly(vinylidene fluoride- co -hexafluoropropylene) (PVDF-HFP) and ZnS particles. The porous film's sensitivity helps the conversion of mechanical disturbances into electrical energies and induces the electroluminescence of ZnS particles. The particle–film interactions induced a high β-phase, which is the most effective piezoelectric phase, in the PVDF-HFP film. Similar to polymeric materials, the composite film is highly processable and can be written into arbitrary shapes or patterns using a pipette or stamping techniques. Finger rubbing or ultrasonication makes the mechanoluminescence patterns readable. This composite mechanoluminescent film provides high potential for future applications in electronic skins, smart electronics, and information encryption techniques.